Cultura e professionalità educative nella società complessa L'esperienza scientifico-didattica della Facoltà di Scienze della Formazione di Firenze Atti del Convegno, 15-17 maggio 2008 - Orefice, Paolo; ULIVIERI, SIMONETTA; Cambi, Franco (Atti, 2010)
The keynote of the recent history of the faculty of educational science of Florence University is change. This has emerged in response to the demands for education expressed by a new knowledge society, spawned by the processes of globalisation, and the social need to foster interculturalism and the dialogue between diversities. In this new dimension of change, education becomes the framework for preparation, but also for re-integrating and updating life itineraries that are swift and precarious, veined with insecurity and disillusionment. Even in the new approach, the scientific and cultural benchmark continues to be a consistent adherence to the secular, historic-pedagogic and educational tradition represented by the masters of the "Florence School". Since its creation in 1996, the new faculty has staked forcefully on the centrality of training in relation to the traditional focus on the professionalism of primary and secondary school teachers, and on the new extra-scholastic training issues: the educational professions; pedagogic care; the social education of adults; the technologies of education and instruction; the philosophic, sociological, psychological and anthropological dimension of education; the broad sphere of hardship and marginalisation and the different faces of diversity.